Association between meteorological factors and reported cases of hand, foot, and mouth disease from 2000 to 2015 in Japan. Issue 14 (22nd August 2017) - SUMI, A.; TOYODA, S.; KANOU, K.; FUJIMOTO, T.; MISE, K.; KOHEI, Y.; KOYAMA, A.; KOBAYASHI, N.
SUMMARY: The purpose of this study was to clarify the association between hand, foot, and mouth disease (HFMD) epidemics and meteorological conditions. We used HFMD surveillance data of all 47 prefectures in Japan from January 2000 to December 2015. Spectral analysis was performed using the maximum entropy method (MEM) for temperature-, relative humidity-, and total rainfall-dependent incidence data. Using MEM-estimated periods, long-term oscillatory trends were calculated using the least squares fitting (LSF) method. The temperature and relative humidity thresholds of HFMD data were estimated from the LSF curves. The average temperature data indicated a lower threshold at 12 °C and a higher threshold at 30 °C for risk of HFMD infection. Maximum and minimum temperature data indicated a lower threshold at 6 °C and a higher threshold at 35 °C, suggesting a need for HFMD control measures at temperatures between 6 and 35 °C. Based on our findings, we recommend the use of maximum and minimum temperatures rather than the average temperature, to estimate the temperature threshold of HFMD infections. The results obtained might aid in the prediction of epidemics and preparation for the effect of climatic changes on HFMD epidemiology.